Metabolomic profiling in a rat model of visual fatigue associated with liver-kidney yin deficiency syndrome - Zhang, Xue; Liu, Xin; Huang, Zhiqiang; Chen, Yan; Zhu, Yingli; Zhang, Jianjun; Du, Jun; Chen, Liang (Frontiers in Endocrinology, 2025)
BackgroundVisual fatigue, commonly attributed to excessive eye use or dry conditions, is traditionally associated with deficiencies in liver and kidney yin in Chinese medicine. However, its metabolic aspects remain largely unexplored.MethodsLevothyroxine sodium combined with tail-clip stimulation induced a rat model of visual fatigue with liver and kidney yin deficiency. At 3 (M1), 7 (M2) and 14 (M3) days after induction, histopathological changes were observed, and metabolic profiling was completed using untargeted UHPLC-Q-Exactive Orbitrap/MS.ResultsThe rats exhibited signs of liver and kidney yin deficiency and visual fatigue on days 3 and 7, respectively. Compared to the control group, we identified 127 and 96 differential metabolites in the serum on days 7 and 14, respectively, primarily lipids and organic nitrogen compounds. Moreover, we observed disruptions in sphingolipid metabolism and signaling pathways.ConclusionThis study enriches our understanding of the metabolic profile associated with liver-kidney-yin deficiency type visual fatigue.